Submissiveness and resistance: Different paradigm between Indonesian language and English - Ma’u, Jean Antunes Rudolf Zico; Fajaruddin, Syarief; Lamahala, Clara Bianrethny Monolga; Fuadi, Choirul; Perdana, Satya; Aryanto, Ardi (LingTera, 2019)
Translation plays greater role in recent time. This phenomenon especially occurs in efforts of bridging meanings and expressions across two different languages or more. In such effort, certainly there should be good understanding toward both the source language and the target language. Unfortunately, the bridge often cannot be constructed well due to the problems of non-equivalence. Therefore, throughout the study the researchers would like to elaborate the techniques that might be used for constructing the bridge between the two languages and the problems that occur during the translation project. In conducting the study, the researchers would strive to translate a copy of presidential decree by applying the selected techniques and by analysing the problems that might appear. The copy of presidential decree had been selected because the copy might not have been available in other languages especially in English. In addition, foreign people and institutions need to learn the decree since they might be doing business that has been associated to the energy in Indonesia. During the study, the researchers applied three techniques and found four problems during the translation project. As conclusion, the researchers found that the three translation techniques have been supporting one to another and the translation problems have been related to the Indonesian culture since the language and culture are inseparable.